Challenges of new food - Lekić, Slavoljub S. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The article draws attention to the development of science and technology in 19th and 20th century, biology and chemistry in particular, and its relation with the green revolution of the middle of 20th century and the gene revolution of the end of 20th century. These two revolutions have resulted in significant changes in food production and integrated agriculture into high technology-based economy.